Big pandemic on the prairie the Spanish Flu in North Dakota - Price, Christopher Neal 1975- (The Digital Press at the University of North Dakota, 2024)
By late September 1918, the Spanish flu began afflicting North Dakotans. Authorities in the state instituted restrictions that affected the daily lives of citizens, including limits on public gatherings and the closing of schools and churches, interventions that resemble those enforced during the recent COVID-19 pandemic. These attempts at mitigating the spread of the flu hit just as politicians began campaigning in a pivotal election that gave full control of the state government to the upstart Nonpartisan League. North Dakota's major newspapers provided a day-to-day accounting of the flu's spread through the state. Native Americans experienced strict quarantines. Nurses provided medicine and sustenance for those afflicted in both urban and rural areas, and purveyors of patent medicines attempted to profit. Big Pandemic on the Prairie traces the history of the disease as it coursed through North Dakota and shaped the history of the state and its communities
Keywords: Influenza Epidemic, 1918-1919 / North Dakota; Pandemics / Government policy / North Dakota; North Dakota / History